Discrete-time output observers for boundary control systems - Emirsajłow, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The paper studies the output observer design problem for a linear infinite-dimensional control plant modelled as an abstract boundary input/output control system. It is known that such models lead to an equivalent state space description with unbounded control (input) and observation (output) operators. For this class of infinite-dimensional systems we use the Cayley transform to approximate the sophisticated infinite-dimensional continuous-time model by a discrete-time infinite-dimensional one with all involved operators bounded.
Keywords: boundary control systems; output observers; infinite-dimensional discrete-time systems